The Dual Burden of Malnutrition and Oral Disease: An Updated Framework for Family Medicine, Dental Care, Nutrition Care, and Community Health Security - Albalawi, Intisar Kalaf; Mugbil Mohammed Alotaibi; Fedha Khamis Nasser Abadi; Ali Bader Alsulami; Azzah Atitallah Ali Alzahrani; Abdullah Ali Mutair Alzahrani; Abdulaziz Saeed Alghamdi; Mohammed Hebah Badawi; Ahmad Abdulsattar Zaghoun; Marwan Saud Alharbi; Mathail Lafi Alanazi (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The aging population faces a complex, bidirectional relationship between oral health and nutritional status. Age-related physiological decline, compounded by oral diseases like periodontitis, caries, and xerostomia, directly impairs masticatory function, leading to poor nutrition. This, in turn, accelerates systemic conditions like sarcopenia and frailty, creating a vicious cycle of decline. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review aims to synthesize an updated framework elucidating the interconnected pathways between oral dysfunction and malnutrition, and to propose integrated, multidisciplinary intervention strategies for family medicine, dental care, and community health. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The article employs a comprehensive literature review methodology, analyzing the impact of specific oral conditions (edentulism, dry mouth, periodontal disease) on dietary intake and nutritional biomarkers. It further examines the shared pathophysiology, such as chronic inflammation, that links oral disease to systemic muscle loss (sarcopenia). <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The analysis confirms that poor oral health is a primary driver of malnutrition in older adults, leading to reduced intake of protein, fiber, and essential micronutrients. Concurrently, oral inflammatory diseases exacerbate systemic inflammation, directly contributing to sarcopenia and frailty, thereby increasing disability and mortality risk. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Breaking the cycle of oral disease and malnutrition requires a collaborative, person-centered approach. Effective management integrates dental rehabilitation, personalized nutrition, and physical therapy within a Comprehensive Geriatric Assessment framework.